Cough fracture: stress on the ribs - Narayanasamy, Sangara Narayanan; Selvaraju, Selvakumaran; Gopalakrishnan, Nirmalkumar; Elumala, Rakeshraj (International Journal of Research in Medical Sciences, 2017)
Cough can be associated with many complications. In this article, we present an 18 year female presenting with cough related stress fracture of the ninth rib. The purpose of this paper is to call attention to an infrequent but possibly often unrecognized cause of pain in the chest of sudden onset and resembling dry pleurisy in its symptoms.